Evaluasi Kinerja Terminal Tipe A Indihiang Kota Tasikmalaya - Malyasari, Nurmela; Hendarto, Sri; Kusdian, Didin (Universitas Ibn Khaldun, 2024)
Indihiang Terminal, a Type A terminal located in Tasikmalaya Regency and was built in 2005 under the management of the Ministry of Transportation and Transportation. This terminal found a fundamental problem: namely the lack of passengers, this has been going on for a long time. Some passengers prefer to depart and get off at bus pools or public roads rather than at the terminal. Research objective to Evaluate terminal performance. Research method: using descriptive quantitative method with Importance Performance Analysis (IPA) and Simple Additive Weighting (SAW) methods. Research sample, The sample used in this study was 64 people. Research results Based on the IPA method, 14 facilities need to be prioritized because, above the iso rating line. Conclusion, Location, accessibility, and onward transportation to or from the Indihiang terminal in Tasikmalaya City are things that need to be improved again and the bus operational system in terms of boarding and dropping passengers needs to be rearranged so that buses pick up and drop off passengers at the terminal.